Persepsi peserta didik kelas IV SD terhadap pembelajaran IPA daring selama masa sindemi - Arrafat, Rahajeng Andriyani Noer; Atmojo, Idam Ragil Widianto; Ardiansyah, Roy (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2021)
This study aims to determine students' perceptions of science learning conductedonline. The method used in this research is descriptive qualitative with a case study approach. The subjects to be researched were students in grade IV SD Angkasa Lanud Adi Soemarmo for the academic year 2020/2021 with a total of 16 students. The research subject was taken by using purposive sampling technique.. The data collection technique was done by interviewing. The data validation used time triangulation. Data analysis was performed using Miles and Huberman through data reduction techniques, data presentation and drawing conclusions.Theresults showed that students felt difficulties in learning science which was carried out through the network (online). The science learning that was carried out during the syndemic period was only in the form of assigning assignments and youtube videos through the whatsapp group owned by the students' parents. The science learning that was carried out during this syndemic period made students not understand what material was provided by the teacher. Science learning which only provides assignments and youtube videos without any explanation about the science material delivered makes students unable to understand the material that the teacher has delivered.